Bow shock clustering in particle-laden wetted cylinder flow. (September 2020) - Shi, Zhaoyu; Jiang, Fengjian; Strandenes, Håkon; Zhao, Lihao; Andersson, Helge I
Highlights: Particle clustering patterns strongly depend on Stokes number in cylinder flow. A particle bow shock observed for the first time in incompressible viscous wake flow. Shape of bow shock investigated via Vorono diagram. Graphical abstract: Abstract: The inhomogeneous distributions of inertial particles in the unsteady flow around a wetted circular cylinder at R e = 100 were investigated in one-way coupled three-dimensional numerical simulations. The Kármán vortex cells determine the local patterns of particle clustering. In the vicinity of the cylinder, a bow shock-like clustering was explored via Voronoï diagrams. The shape of the bow shock in terms of width and thickness strongly depends on Stokes number, Sk. For high-Sk particles, the bow shock was wider and less affected by the vortex shedding in the near wake and thus extended further downstream. We tracked low-Sk particles in a steady potential flow aimed at mimicking the viscous flow field close to the cylindrical surface. The converging tendency of the particle trajectories at the upstream of the cylinder supported the appearance of a bow shock. Furthermore, we analysed the trajectory of a Sk=0.1 particle in viscous flow, wherein the direction of the perpendicular component of the Stokes drag force was altered from outwards to inwards at the inflection point of the trajectory. This observation suggests that the centrifugal mechanism makes particle trajectories converge and thereby contributes to the formation of the bow shock.